"Tell Me About Your Picture": Using Drawings to Support Expressive Language in Children With Autism Spectrum Disorder. (November 2020) - Wright, Bridget M.; Benigno, Joann P.; Boster, Jamie B.; McCarthy, John W.; Coologhan, Bridget K.
Thirty-one children with and without autism spectrum disorder were asked to draw the meaning of 10 basic concepts. Following each drawing, children explained their drawing to the experimenter. Transcripts of the drawing task were coded for children's use of personal pronouns and internal state terms. Children's use of on- and off-task comments while explaining each drawing was examined. Both groups of children had a longer mean length of utterance when prompted to explain their drawings than while they were drawing. Analyses revealed no significant differences between children with and without autism in their use of internal state terms, pronouns, or their use of on- and off-task language during the drawing task. Clinical implications for the use of drawings as expressive language supports for children with autism are discussed.